(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Thailand has the highest growth rate of electronic retail business in ASEAN (ETDA, 2019). When faced with the epidemic crisis of Corona Virus Disease 2019, it resulted in the competition which intensified even more. As a consequence, it is challenging for eretailing businesses to gain success. This paper is aimed at examining the effects of individual marketing strategy on excellence experience creation, marketing value achievement, individual satisfaction fulfillment, and marketing profitability of e-retailing businesses in Thailand. Using a mailed survey of 139 e-retailing businesses located throughout Thailand as the key instrument to collect data, the model is empirically tested. Correlation analysis and multiple regression analysis are used to analyze data. The findings suggest that all three dimensions of individual marketing strategy have a significant positive influence on excellence experience creation, marketing value achievement, individual satisfaction fulfillment, and marketing profitability. However, it is evident that marketing operation flexibility has no influence on marketing profitability. In addition, excellence experience creation, marketing value achievement, and individual satisfaction fulfillment have an influence on marketing profitability. Finally, this study suggests theoretical and managerial contributions to academics and executives of e-retailing businesses operated under a crisis environment so as to gain marketing profitability and business survival. Recommendations for future research are also provided.